1997
DOI: 10.1063/1.1148194
|View full text |Cite
|
Sign up to set email alerts
|

Contrast and resolution in imaging with a microfocus x-ray source

Abstract: A simple general treatment of x-ray image formation by Fresnel diffraction is presented; the image can alternatively be considered as an in-line hologram. Particular consideration is given to phase-contrast microscopy and imaging using hard x rays. The theory makes use of the optical transfer function in a similar way to that used in the theory of electron microscope imaging. Resolution and contrast are the criteria used to specify the visibility of an image. Resolution in turn depends primarily on the spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
300
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(311 citation statements)
references
References 32 publications
4
300
0
7
Order By: Relevance
“…[15] The simplest such method is the free-space propagation technique, which has been discussed extensively in the literature. [21][22][23][24][25][26][27][28][29] Briefly, a plane-wave or spherical-wave with high spatial coherence is incident on the object under study. Features in the object that correspond to sharp changes in the wave phase refract and diffract the x-rays.…”
Section: Phase-contrast X-ray Imagingmentioning
confidence: 99%
“…[15] The simplest such method is the free-space propagation technique, which has been discussed extensively in the literature. [21][22][23][24][25][26][27][28][29] Briefly, a plane-wave or spherical-wave with high spatial coherence is incident on the object under study. Features in the object that correspond to sharp changes in the wave phase refract and diffract the x-rays.…”
Section: Phase-contrast X-ray Imagingmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Recent advances in phase-contrast enhanced x-ray imaging using laboratory x-ray sources makes x-ray imaging of the solid D-T layer possible. [16][17][18] Calculations for phase-contrast x-ray imaging showed that the D-T surface should be rendered visible in the Be(Cu) shell using a micro-focus source. [7] Models also demonstrate that the surface roughness can be accurately characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [45] estimated ÎŽ and ÎČ values for biological tissues, where it was further shown that ÎŽ is around 1000 times stronger than ÎČ in the X-ray range of 10-100 keV [48,49]. This also implies that the difference in terms of ÎŽ between two given tissues are larger, than the differences in ÎČ, thus suggesting that X-ray based PhC-imaging is more sensitive, than standard Abs-imaging [50,51,52,48,49,53] Figure 12: Illustration of the diffraction of X-rays for Absorption vs. propagation based imaging, for various sample-to-detector distances, z, where λ is the X-ray wavelength and d is the size of a sample structure orthogonally to the beam direction [47]. Allowing the diffracted X-rays to propagate the short altered distance z beyond the sample a Fresnel diffraction will occur, under the circumstances that z ∌ d 2 /λ [50,47].…”
Section: Imaging Modesmentioning
confidence: 99%